South African Trade Union responses to xenophobia in workplaces: the National Union of Mineworkers (NUM) and the National Union of Metalworkers of South Africa (NUMSA) - Gongqa, Nombulelo (Rhodes University, Faculty of Humanities, Department of Sociology, 2019)
This research looks at how trade unions relate to immigrants and how inclusive they are to immigrants who form part of the South African working class. South Africa has been an immigrants receiving country for decades, where most immigrants are from neighbouring countries within the South African region. It was the trade unions that empowered workers to gain back some of their basic rights during the apartheid era, and they did this for all workers who worked in sectors where they were exploited and mistreated by the apartheid regime on the basis of their skin colour. This research aims to understand how trade unions respond to xenophobia in the workplace, and the ways their strategies increase inclusion of immigrants in the trade unions. This research focuses on the National Union of Mineworkers (NUM) and the National Union of Metalworkers of South Africa (NUMSA), seeking to find whether they have strategies and planned ways to respond to xenophobia in South African workplaces. This research also looks at the impact of nationalism in South Africa on immigrants. It shows that whilst the concept of nationalism is to protect South Africans, it does exclude immigrants because it places South Africans before immigrants when it comes to benefiting from the resources of the country. This shows that protecting one section of the working class over another weakens the working class movement. To get views from the trade unions, trade union officials were interviewed and from the interviews, common themes were picked out. From the interviews, it can be identified that trade union officials believe that immigrants should be included in the trade unions, and they should be treated with dignity. However, there are some conflicting themes, which highlight the view that South African locals deserve to get the resources of the country, such as housing, before immigrants. The themes will be discussed in the research to highlight the different perspectives that came from the trade union officials.
Keywords: Xenophobia; Xenophobia-- -- South Africa; National Union of Mineworkers; National Union of Metalworkers of -- South Africa; Labor unions -- South Africa; Immigrants -- South Africa; Marginality, Social -- South Africa; Social conflict -- South Africa